Ablation index-guided high-power ablation for superior vena cava isolation in patients with atrial fibrillation - Cui, Luqian; Cui, Shihua; Dong, Shujuan; Li, Jingchao; Yu, Haijia; Song, Huihui; Han, Yongmei; Chu, Yingjie (Frontiers in Cardiovascular Medicine, 2022)
Background The strategy of ablation index (AI)-guided high-power ablation seems to be a novel strategy for performing pulmonary vein isolation (PVI). An AI-guided high-power ablation strategy was used in this study to determine whether superior vena cava isolation (SVCI) after PVI was feasible and safe for patients with AF. Methods Data from 53 patients with AF were collected. Mapping and ablation of SVC were performed. The applied power was set at 45 W and the procedure was guided by AI. The SVC was divided into six segments in a cranial view. The RF applications and AI values in different segments were compared and analyzed. Using receiver operating characteristic (ROC) analysis, the diagnostic accuracy of AI value for predicting segment block was evaluated. Results Electrical SVCIs were successfully achieved in all patients. SVCI was performed by segment ablation in most cases, with RF applications in different segments. The mean AI value in non-lateral walls was higher than that of the lateral wall (392 ± 28 vs. 371 ± 37, P < 0.001). Acutely blocked sites had significantly larger AI values compared with no-blocked sites (390 ± 30 vs. 343 ± 23, P < 0.001). The optimal AI cut-off value for non-lateral segments was 379 (sensitivity: 75.9%, specificity: 100%) and for lateral segments was 345 (sensitivity: 82.3%, specificity: 100%). Conclusion The AI values were predictive of the acute conduction block of SVCI. With AI values of 345 and 379, respectively, conduction block was achieved in the lateral walls at a lower level than in the non-lateral walls.